Assessment of the structural evolution of polyimide-derived carbons obtained by phosphoric acid activation using Fourier transform infrared and Raman spectroscopy - Alexander M Puziy; Olga I Poddubnaya; Magdalena Sobiesiak; Barbara Gawdzik (Adsorption Science & Technology, 2017)
Two series of carbons obtained by carbonization of porous copolymer of 4,4′-bis(maleimidodiphenyl) methane (50 mol%) and divinylbenzene (50 mol%) with and without phosphoric acid (impregnation ratio 1.1) at temperatures 400–1000℃. The carbons were characterized using elemental analysis, nitrogen adsorption, potentiometric titration, Fourier transform infrared and Raman spectroscopy. It has been shown that phosphoric acid causes structural and chemical changes in polyimide copolymer as compared to thermally treated carbons. Structural changes: phosphoric acid promotes transformation of polyimide copolymer to carbon structure at lower temperatures as compared to thermally treated carbons. Phosphoric acid is responsible for formation of highly developed micro/mesoporous structure that is different from that of thermally treated carbons. Chemical changes: phosphoric acid causes elimination of hydrogen and nitrogen, introduction of phosphorus and oxygen as phosphate-like structure. Significant amount of phosphorus imparts acid properties to carbon.